Effect of pyrites on yield and mineral composition of wheat (Triticum aestivum) irrigated with sodic water - RAM, S; PAL, B (The Indian Journal of Agricultural Sciences, 2013)
A micro-plot experiment was conducted during winter seasons (rabi) of 1987-88,1988-90 and 1989-90 at Bichpuri. Agra, to evaluate the efficacy and suitability of different methods of pyrites application on yield and mineral composition of wheat (Trilicum aestivum L. emend. Fiori & Paol). The methods comprised total quantity of pyrites for 6 irrigations @ 1.32, 2.63 and 3.94 tonneS/ha mixed in soil a week before presowing irrigation; cumiutative application of pyrites @ 0.22, 0.44 and 0.66 tonne/ha as top-dressing for 1 irrigation, before each irrigation; and pyrites application @ 0.22. 0.44 and 0.66 tonne/ha for 1 irrigation. dissolved in irrigation water with. each irrigation to reduce residual sodium carbonate of irrigation waterfrom 20 to 15, 10 and 5.0 meq/litre respectively. Significant increase was noted in grain and straw yields. and nitrogen. potassium and sulphur content in grain and straw both at crop maturity when total quantity of 3.94 tonnes/ha of pyrites was used for 6 irrigations milted in soil a week before presowing irrigation to reduce residual sodium carbonate from 20 to 5.0 meq/litre compared wilh sodic water treatment (residual.sodium carbonate 20 meq/litre) during 1988-89 and 1989-90 only. However, the grain and straw yields increased gradually with increase in the dose of pyrites by all the methods to reduce residual sodium carbonate of irrigation water compared with sodic water application during all the years. Pyrites applicationbefore presowing irrigation proved better than the other methods in minimizing the adverse effect of sodic water. Soil pH and exchangeable sodium (%) decreased and hydraulic conductivity increased appreciably with increase in pyrites level compared with sodic water application (20 meq/litre). Maximum reduction was 2.22.16.13 and 18.28%in soil pH and 22.55. 64.36 and 73.44% in exchangeable sodium (%) of surfacesoil (0-15 em) during 1988. 1989 and 1990 respectively, when total quantity of pyrites @ 3.94 tonnes/ha was mixed. in soil for 6 irrigations compared with sadic waler application without pyrites.